Education on a Balanced Nutritional and Anemia in Adolescents in Ampana Tete District: Edukasi Gizi Seimbang dan Anemia pada Remaja di Kecamatan Ampana Tete - Dwi Erma Kusumawati; Ansar; Wery Aslinda; Diah Ayu Hartini (Poltekkes Kemenkes Palu, 2022)
The female adolescent is an important target for stunting reduction efforts. Adolescence is a pubertal phase with fast physical, psychological, and social growth and development. Unicef reported in Adolescent Profile 2021 that 40% of adolescents aged 15-19 yo who have low food consumption variety is related to economic factors. This community service was a balanced nutrition and anemia education among female adolescents at Ampana Tete Sub-District, Tojo Una-Una Regency. This community service was conducted in two villages (Bantuga and Uebone). Activities conducted are balanced nutrition and anemia education, distribution of iron supplement tablets, and promotion of “My Meal Plate” by using the banner. The result of pre and post-test showed that the knowledge of female adolescents was increased after conducting education.